2015
DOI: 10.1111/evo.12774
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs in osmoregulation and parallel shifts in molecular function follow ecological transitions to freshwater in the Alewife

Abstract: Adaptation to freshwater may be expected to reduce performance in seawater because these environments represent opposing selective regimes. We tested for such a trade-off in populations of the Alewife (Alosa pseudoharengus). Alewives are ancestrally anadromous, and multiple populations have been independently restricted to freshwater (landlocked). We conducted salinity challenge experiments, whereby juvenile Alewives from one anadromous and multiple landlocked populations were exposed to freshwater and seawate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 64 publications
(198 reference statements)
3
68
2
Order By: Relevance
“…PCR conditions were maintained at: 95˚C for 2 minutes for polymerase activation and 40 cycles (denaturation at 95˚C for 5 seconds, annealing at 58-62˚C for 20 seconds and an extension step at 72˚C for 20 seconds). Relative gene expression values were then obtained using a delta-delta method following standard protocols (Pfaffli, 2001;Velotta et al, 2015). Relative gene expression values were analyzed in SPSS (version 22) at 5% level of significance.…”
Section: Rt-qpcr Assay For the Validation Of Differential Gene Expresmentioning
confidence: 99%
See 4 more Smart Citations
“…PCR conditions were maintained at: 95˚C for 2 minutes for polymerase activation and 40 cycles (denaturation at 95˚C for 5 seconds, annealing at 58-62˚C for 20 seconds and an extension step at 72˚C for 20 seconds). Relative gene expression values were then obtained using a delta-delta method following standard protocols (Pfaffli, 2001;Velotta et al, 2015). Relative gene expression values were analyzed in SPSS (version 22) at 5% level of significance.…”
Section: Rt-qpcr Assay For the Validation Of Differential Gene Expresmentioning
confidence: 99%
“…To date however, little work has been directed at identifying and characterizing genes and pathways that facilitated crustacean adaptation to freshwater environments. A number of studies of fish have concluded that changes to expression of osmoregulatory genes have played the principal roles in driving this process (DeFaveri et al, 2011;DeFaveri and Merila, 2014;Brennan et al, 2015;Velotta et al, 2015;Velotta et al, 2017). Crustaceans unlike most vertebrates often possess complex life cycles that involve many developmental stages in different habitats.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations